2020
DOI: 10.1186/s13054-020-2795-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of protocolized diuresis for de-resuscitation in the intensive care unit

Abstract: Objective: Administration of diuretics has been shown to assist fluid management and improve clinical outcomes in the critically ill post-shock resolution. Current guidelines have not yet included standardization or guidance for diuretic-based de-resuscitation in critically ill patients. This study aimed to evaluate the impact of a multi-disciplinary protocol for diuresis-guided de-resuscitation in the critically ill. Methods: This was a pre-post single-center pilot study within the medical intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 26 publications
3
52
0
Order By: Relevance
“…Prior studies have demonstrated that most fluids administered in critical care are given with medications rather than as bolus or maintenance crystalloid [ 33 , 34 ]. Our study corroborates these findings that crystalloid used for resuscitation is typically a less significant contributor to net fluid balance than diuretic use and incidental fluids in the ARDS population [ 29 , 35 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…Prior studies have demonstrated that most fluids administered in critical care are given with medications rather than as bolus or maintenance crystalloid [ 33 , 34 ]. Our study corroborates these findings that crystalloid used for resuscitation is typically a less significant contributor to net fluid balance than diuretic use and incidental fluids in the ARDS population [ 29 , 35 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…In a multicentric cohort of patients with acute kidney injury [19], the use of diuretics was associated with increased mortality by day-60. However, in more recent cohorts [26,27], diuretics were associated with decreased mortality and improved kidney function. Thus, the use of diuretics in the ICU to control fluid balance could be promising, but there is little evidence regarding the benefit/risk ration of this medication in critically ill patients.…”
Section: Discussionmentioning
confidence: 94%
“…In Give and Take, Adam Grant discusses the power of an individual's professional generosity to support wellness and future success 26 . Teaching, which combines both intellectual engagement of conveying complex material with the power of connection, may be a powerful protector against burnout while also serving as a meaningful way to optimize patient outcomes 37‐40 . Identifying strategies to maximize this vital role of the critical care pharmacist in the health care setting is warranted.…”
Section: Discussionmentioning
confidence: 99%